Bio-efficacy of pre and post- emergence herbicides on weed management, growth and yield of transplanted scented rice under lower Gangetic alluvial zone - Murmu, Kanu; Das, Priya; Mondal, Bikas; Sarkar, Arup (ORYZA-An International Journal of Rice, 2025)
During the kharif seasons of 2018-19 and 2019-20, field work was conducted at the Jaguli Instructional Farm at the Bidhan Chandra Krishi Viswavidyalaya in Mohanpur, Nadia, West Bengal, conducted a field experiment to determine the most effective pre- and post-emergence herbicides for controlling weeds and maximizing yields of the scented rice variety Gobindabhog that had been transplanted. Lower density and biomass with greater weed control efficiency resulted in a 3.30 t ha-1 grain yield from hand weeding (HW) twice at 20 and 40 days after transplanting (DAT), followed closely by Pretilachlor at 1.5 kg a.i. ha-1 as pre-emergence PE (2 DAT) fb Bispyribac Sodium @ 40.0 g a.i ha-1 as post-emergence POE (20 DAT). Unweeded check had a 42.12% decrease in grain yield compared to Hand weeding twice, perhaps due to the presence of weeds.